2023
DOI: 10.1044/2023_jslhr-23-00279
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Velopharyngeal Anatomy of 9- and 10-Year-Old Children

Jamie L. Perry,
Myoung Keun Lee,
Neda Tahmasebifard
et al.

Abstract: Objective: Understanding the normal anatomy of velopharyngeal (VP) mechanism and the emergence of sexual dimorphism provides valuable insights into differences of VP anatomy among males and females. The purpose of this study is to examine sex differences in VP anatomy in a large data set of 3,248 9- and 10-year-old children. Method: Static three-dimensional magnetic resonance imaging was used to compare five VP characteristics including v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This is particularly relevant, given that recent studies have noted that small quantitative differences (<1 mm) have been reported to influence velopharyngeal function, and these differences may be correlated with the perception of hypernasality. 56,57 For example, in patients that demonstrate velopharyngeal insufficiency, use of the curvilinear measurement provides more accurate quantitative assessment of the velar morphology and likelihood for postoperative VP function, particularly as it relates to distraction osteogenesis 30 and obstructive sleep apnea. 58 Furthermore, functional differences may also be observed when assessing velar length during phonation due to patient-specific anatomy postpalatoplasty, again highlighting the need to precisely measure this structure using a curvilinear measurement.…”
Section: Table 1 Velopharyngeal Variables Of Interestmentioning
confidence: 99%
“…This is particularly relevant, given that recent studies have noted that small quantitative differences (<1 mm) have been reported to influence velopharyngeal function, and these differences may be correlated with the perception of hypernasality. 56,57 For example, in patients that demonstrate velopharyngeal insufficiency, use of the curvilinear measurement provides more accurate quantitative assessment of the velar morphology and likelihood for postoperative VP function, particularly as it relates to distraction osteogenesis 30 and obstructive sleep apnea. 58 Furthermore, functional differences may also be observed when assessing velar length during phonation due to patient-specific anatomy postpalatoplasty, again highlighting the need to precisely measure this structure using a curvilinear measurement.…”
Section: Table 1 Velopharyngeal Variables Of Interestmentioning
confidence: 99%